Pengungkapan Sustainability Reporting dengan Efek Profitabilitas dan Mekanisme Good Corporate Governance - Sasa S. Suratman; Mochammad Ridwan; Aliza Pravitasari Putri (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2023)
This study aims to examine the influence of profitability and good corporate governance mechanisms on sustainability reporting disclosure in State-Owned Enterprises listed on the Indonesia Stock Exchange. The research method employed in this study is multiple linear regression analysis. The population of the study consists of 677 companies, and a sample of 13 companies is selected using sampling techniques. The observation period for this study ranges from 2015 to 2019, resulting in a total of 65 data observations. The findings of the study indicate that profitability and the audit committee have a positive influence on sustainability report disclosure, while the board of commissioners does not have a significant impact on sustainability report disclosure. Collectively, profitability, the board of commissioners, and the audit committee have an influence on sustainability report disclosure in State-Owned Enterprises listed on The Indonesia Stock Exchange.